Emerging roles of ECM remodeling processes in cancer. (May 2020) - Mohan, Vishnu; Das, Alakesh; Sagi, Irit
Abstract: Extracellular matrix (ECM) plays a central and dynamic role in the creation of tumor microenvironment. Herein we discuss the emerging biophysical and biochemical aspects of ECM buildup and proteolysis in cancer niche formation. Dysregulated ECM remodeling by cancer cells facilitate irreversible proteolysis and crosslinking, which in turn influence cell signaling, micro environmental cues, angiogenesis and tissue biomechanics. Further, we introduce the emerging roles of cancer microbiome in aberrant tumor ECM remodeling and membrane bound nano-sized vesicles called exosomes in creation of distant pre-metastatic niches. A detailed molecular and biophysical understanding of the ECM morphologies and its components such as key enzymes, structural and signaling molecules are critical in identifying the next generation of therapeutic and diagnostic targets in cancer.